2018
DOI: 10.1002/cbdv.201800119
|View full text |Cite
|
Sign up to set email alerts
|

Sprouted and Freeze‐Dried Wheat and Oat Seeds – Phytochemical Profile and in Vitro Biological Activities

Abstract: This research was carried out to study phytochemical profile, in vitro antioxidant capacity, reducing power, anti-hyperglycemic, anti-inflammatory activities and simulated gastrointestinal digestion of 7-day old cereal sprouts: spelt wheat 'Nirvana' (WSSpe), wheat 'Simonida' (WSSim), oat 'Golozrni' (OSG) and oat 'Jadar' (OSJ). OSG expressed significantly higher (P ≤ 0.05) total phenols (TPC) and flavonoids content (TFC), antioxidant capacities (DPPH and ABTS assays) and reducing power (EC = 2.12 mg/ml; EC = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
2
21
2
Order By: Relevance
“…For the hydroxycinnamic acids, coumaric acid isomer II was the main moiety; ferulic acid and its hexoside, as well as the feruoylquinic acid isomer I, were also present in an abundant proportion. Aborus and collaborators [16] also identified Foods 2020, 9, 169 13 of 21 these phenolic compounds in sprouted oats of the Golozrni and Jadar varieties, with p-hydroxybenzoic and sinapic acids being their principal acids; however, in the Turquesa oat variety, we additionally identified hexoside compounds, isoflavones, and phytosterols. In the same report, myricetin and kaempferol were the principal flavonoids, while in our study, hexoside forms of both compounds were predominant in the Turquesa sprouted oat variety.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For the hydroxycinnamic acids, coumaric acid isomer II was the main moiety; ferulic acid and its hexoside, as well as the feruoylquinic acid isomer I, were also present in an abundant proportion. Aborus and collaborators [16] also identified Foods 2020, 9, 169 13 of 21 these phenolic compounds in sprouted oats of the Golozrni and Jadar varieties, with p-hydroxybenzoic and sinapic acids being their principal acids; however, in the Turquesa oat variety, we additionally identified hexoside compounds, isoflavones, and phytosterols. In the same report, myricetin and kaempferol were the principal flavonoids, while in our study, hexoside forms of both compounds were predominant in the Turquesa sprouted oat variety.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, cereal sprouts have received considerable attention as functional foods in many countries, especially in Europe, the United States of America, and Japan, due to their superior nutritious and health benefits compared to seeds [16]. The germination of cereals has been used for centuries to soften kernel structure, decrease the content of antinutritive compounds, and to increase nutrient content and availability [17].…”
Section: Introductionmentioning
confidence: 99%
“…The presented results (Figure 3 protein denaturation by QW extract and DS throughout the concentration range of 0.25 to 20 mg/ml. Aborus et al (32) reported the EC 50 values from 2.77 mg/ml to 4.77 mg/ml for 7-day old cereal sprouts (two oat cultivars, 'Golozrni' and 'Jadar', two wheat cultivars, spelt 'Nirvana' and 'Simonida'). Ullah et al (33) studied the AIA of Curcuma zedoaria rhizome extract and found an EC 50 value of 300 μg/ml.…”
Section: Figure 2 Reducing Power Of Qw Extractmentioning
confidence: 99%
“…The biological effects of PC depend principally on their bioaccessibility (release of the food matrix in an absorbable form during digestion) and bioavailability (absorption and transference to the bloodstream), and both depend on their chemical structure, matrix interactions, antioxidant activity, and food processing (7379). Natural PC usually occur as glycosides, esters or polymers that have no biological activity (80).…”
Section: Nutritional Valuementioning
confidence: 99%